Resistance to medically important antimicrobials in broiler and layer farms in Cameroon and its relation with biosecurity and antimicrobial use - Ronald Vougat Ngom; Ronald Vougat Ngom; Andrea Laconi; Roberta Tolosi; Adonis M. M. Akoussa; Stephane D. Ziebe; Vincent M. Kouyabe; Alessandra Piccirillo (Frontiers in Microbiology)
IntroductionPoultry production accounts for 42% of Cameroonian meat production. However, infectious diseases represent the main hindrance in this sector, resulting in overuse and misuse of antimicrobials that can contribute to the emergence and dissemination of antimicrobial resistance (AMR). This study aimed to evaluate the prevalence of antimicrobial resistance genes (ARGs) conferring resistance to carbapenems (blaVIM-2 and blaNDM), (fluoro) quinolones (qnrS, qnrA, and qnrB), polymyxins (mcr1 to mcr5), and macrolides (ermA and ermB) in the poultry farm environment. Additionally, the study examined the relationship between these ARGs and biosecurity implementation, as well as farmers’ knowledge, attitudes, and practices toward antimicrobial use (AMU) and AMR, including their perception of AMR risk.Materials and methodsFecal, drinking water, and biofilm samples from drinking water pipelines were collected from 15 poultry farms and subsequently analyzed by real-time PCR and 16S rRNA NGS.ResultsAll samples tested positive for genes conferring resistance to (fluoro) quinolones, 97.8% to macrolides, 64.4% to polymyxins, and 11.1% to carbapenems. Of concern, more than half of the samples (64.4%) showed a multi-drug resistance (MDR) pattern (i.e., resistance to ≥3 antimicrobial classes). Drinking water and biofilm microbial communities significantly differed from the one of the fecal samples, both in term of diversity (α-diversity) and composition (β-diversity). Furthermore, opportunistic pathogens (i.e., Comamonadaceae and Sphingomonadaceae) were among the most abundant bacteria in drinking water and biofilm. The level of biosecurity implementation was intermediate, while the knowledge and attitude of poultry farmers toward AMU were insufficient and unsuitable, respectively. Good practices toward AMU were found to be correlated with a reduction in polymyxins and MDR.DiscussionThis study provides valuable information on resistance to medically important antimicrobials in poultry production in Cameroon and highlights their potential impact on human and environmental health.